Comunicação, consumo e diversão nos vídeos unboxing: a publicidade e a criança conectada - Andrade, Marcelo de (2019)
Based on the fact that children are progressively inserted in the digital communication channels, both consuming and producing content, the present research aimed to problematize a specific type of media production that has been attracting increasing attention and raising a significant new adepts in recent years: the so-called unboxing videos, whose free translation would be "out of the box." In child-oriented channels on online platforms such as YouTube, children display toys being unpacked gradually in front of the camera, demonstrating fun and relaxed product details and modes that are considered "right" and "desirable" to play. To reflect on communication and consumption of the ways of being children promoted in these media platforms, we analyzed in this study the channels of two young youtubers whose productions include videos of the unboxing type. We understand unboxing videos as a format that unsettles play and advertising, and the channels of youtubers are a fertile ground for the propagation of brands and products. We work with the methodology of critical analysis, which describes and interprets what it observes in the empirical field based on the theoretical-conceptual basis of the research. It is worth remembering that the offer of products directly from the market to the children's public has become complex mainly due to two factors: the first concerns the limits imposed by the regulation of advertising directed at children in Brazil. The second factor is related to the fact that marketing communication enters the daily life of the child without many times necessarily perceiving it as such. In this scenario, the border between entertainment and publicity is blurring the distinction and, therefore, the regulation of advertising communication in the digital spaces. Although we understand the connected child not as a helpless being, but as an active subject who appropriates with remarkable ease of online environments to communicate, socialize and have fun, we find worrying the lack of regulation of promotional practices and related in these environments.